Strengthening the climate services chain in Central America - Martínez Barón, Deissy; Navarro-Racines, Carlos Eduardo; Martínez, Jesús David; González Romero, Carmen; Muñoz, Angel G; Castellanos, Andrea; Giraldo Mendez, Diana Carolina; Prager, Steven D; Ramírez Villegas, Julián Armando (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Central American farmers are highly vulnerable to climate variability, with crop losses observed throughout the region on a virtually annual basis. At the same time, local stakeholders and farmers generally have limited access to existing climate and forecast information, do not have sufficient capacities to understand the climate information and/or mechanisms to relate this information to the impact that climate variations can generate at the local level. This precludes the translation of information into actionable knowledge, and therefore into action.